BARBOTAGE CHEMICAL EFFECTS: THEIR TYPES, MECHANISMS OF OCCURRENCE AND GEOCHEMICAL MANIFESTATIONS - Кушнір, С. В.; Кость, М. В.; Козак, Р. П. (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2016)
The changes of pH and Eh in water and aqueous NaCl – solutions at 20 °C during the transmission of pure gases (N2, O2, air, CO2) in different modes of barbotage are experimentally investigated. The results are analyzed taking into account modern notions of the structure of liquid water and its surface (interface). Generally, the barbotage process consists of two stages: I – the first 10 minutes with the rapid increasing in pH and decreasing in Eh due to leaching of dissolved CO2 and O2; II – up to 2-3 hours when Eh continues to decrease slowly, but pH can increase (alkaline BCE) or decrease (acid BCE), indicating the acidic nature of gas/water surface and aerosols produced during barbotage. Special experiments on the magnetic stirrer showed that noticeable changes in pH and Eh begin only after the transition from laminar regime of mixing to turbulent, which leads to a significant increasing of the structural temperature of water and a corresponding reduction in the solubility of oxygen and Eh values. This is the main reason for the changes at the first step of barbotage, which can be called as the turbulent BCE. We must highlight the differentiation of ions during barbotage in mixed salt solutions. To explain this phenomenon of ion BCE, the hypothesis of neutral ion pairs has been proposed and substantiated, which satisfactorily explains the genesis and properties of marine aerosols.